2020
DOI: 10.1029/2020ef001516
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Explicit Inventory of Sources of Nitrogen Inputs to the Yellow Sea, East China Sea, and South China Sea for the Period 1970–2010

Abstract: Symptoms of eutrophication (including biodiversity loss, harmful algal blooms, and hypoxia) are an increasing problem in Chinese seas. Nutrient enrichment is primarily caused by accelerated human activities that cause nutrient pollution of the aquatic environment. In this study, the Integrated Model to Assess the Global Environment-Global Nutrient Model (IMAGE-GNM) was used to estimate nitrogen inputs from river discharge, submarine fresh groundwater discharge, and mariculture, and TM5-FAst Scenario Screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 74 publications
3
37
0
Order By: Relevance
“…In addition, this sediment denitrification flux is proportionate to ∼7.5% of global marine benthic denitrification (124 Tg N yr −1 [Bianchi et al., 2012]). N inputs from river export, atmospheric deposition, mariculture, and submarine fresh groundwater discharge to the coastal waters of China are estimated to be 10.42 Tg year −1 , with the contribution of river export to total N inputs is in excesses 80% (Wang et al., 2020). Although the potential denitrification flux of sediments near the estuaries of three largest rivers of China was likely underestimated in our study, because we assumed N 2 production rate by denitrification was zero in winter, it was comparable to total N inputs in coastal waters of China.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, this sediment denitrification flux is proportionate to ∼7.5% of global marine benthic denitrification (124 Tg N yr −1 [Bianchi et al., 2012]). N inputs from river export, atmospheric deposition, mariculture, and submarine fresh groundwater discharge to the coastal waters of China are estimated to be 10.42 Tg year −1 , with the contribution of river export to total N inputs is in excesses 80% (Wang et al., 2020). Although the potential denitrification flux of sediments near the estuaries of three largest rivers of China was likely underestimated in our study, because we assumed N 2 production rate by denitrification was zero in winter, it was comparable to total N inputs in coastal waters of China.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we leverage a ∼2,500 km continental shelf sediment transect along coastline in eastern China to explore sedimentary denitrification and anammox processes and their controlling factors (Figure 1). Anthropogenic reactive N inputs in this region have substantially increased over the past 40 years (Wang et al., 2020). A large amount of N in the rivers is delivered to the sea via terrestrial runoff (Liu et al., 2018; Tao et al., 2010), which contributes to the abnormal proliferation of algae and eutrophication of seawaters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seasonal NO 3 − budgets from the numerical model indicated that the atmospheric flux was much lower than other sources although the flux did not consider tempo-spatial variation. However, recent studies revealed that the contribution of atmospheric deposition to NO 3 − budgets in the YS continues to increase due to anthropogenic activity (Zhang et al, 2007;Luo et al, 2018;Wang et al, 2020). Thus, the impact of a recent increase in the atmospheric deposition on budgets in the YS will be investigated through regular observation and an atmospheric-ocean coupled model.…”
Section: Limitations Of the Modelmentioning
confidence: 99%
“…Another N source to the TWS is atmospheric deposition. Atmospheric N deposition to the whole strait during 2001-2010 was estimated as 135.6 ± 12.6 Gg yr −1 based on study by Wang et al (2020), accounting for less than 5.5% of all DIN input to the TWS (see result 3.5); as atmospheric N was relatively unimportant, it was not included in the modeling. Small rivers in the region (both Chinese mainland and Taiwan) with less runoff were not considered as their influence in the TWS is small (Wang et al, 2013).…”
Section: Modeling Approachmentioning
confidence: 99%